3 - Towards an Environmental Communication Conceptual Model for Enabling Socio-economic Development in Africa - Kwamena Kwansah-Aidoo, (Africa Media Review, 2004)
Africa has vast natural and human resources and thus great potential for socioeconomic development. Yet, very few countries on the continent have been able to utilise their resources fully and to reap the expected benefits from that potential. Many of the factors for this failure to boost socio-economic development and improve the lives of individuals and groups on the continent have been well documented. However, one factor that is often glossed over is the role of negative environmental behaviour on development. This paper argues that there is a strong relationship between the two and suggests a viable framework for integrating these two issues/ areas by providing a theoretical model for incorporating environmental communication, and subsequently environmental consciousness, into socio-economic development programmes.